The Influence of Compensation, Work Motivation, and Work Discipline on the Performance of PT Marinal Employees - Widya Fatmasari; Beureukat; Adam Nurkholik; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2023)
This study aims to find out and analyze the effect of compensation, work motivation, and work discipline on the performance of PT Marinal's employees. This study uses primary data through distributing questionnaires. The population in this study is 84 employees. The sampling technique is using saturated sampling technique in which the population of employees of PT Marinal is used as a sample. The analytical method used is multiple linear regression analysis using the SPSS 23 program. The results of the study show that there is a positive and significant effect between compensation and employee performance, work motivation has a positive and significant effect on employee performance, and work discipline has a positive and significant effect on employee performance.